Value of electrocardiogram in diagnosing right ventricular involvement in patients with an acute inferior wall myocardial infarction. Issue 4 (April 1983) - Braat, S H; Brugada, P; de Zwaan, C; Coenegracht, J M; Wellens, H J
Abstract : To study the value of the electrocardiogram in diagnosing right ventricular involvement in acute inferior wall myocardial infarction, the electrocardiographic findings were analysed in 67 patients who had had scintigraphy to pin-point the infarct. All 67 patients were consecutively admitted because of an acute inferior wall infarction. A 12 lead electrocardiogram with four additional right precordial leads (V3R, V4R, V5R, and V6R) was routinely recorded on admission and every eight hours thereafter for three consecutive days. Thirty-six to 72 hours after the onset of chest pain a 99mtechnetium pyrophosphate scintigraphy and a dynamic flow study were performed to detect right ventricular involvement, which was found in 29 of the 67 patients (43%). ST segment elevation greater than or equal to 1 mm in leads V3R, V4R, V5R, and V6R is a reliable sign of right ventricular involvement. ST segment elevation greater than or equal to 1 mm in lead V4R was found to have the greatest sensitivity (93%) and predictive accuracy (93%). The diagnostic value of a QS pattern in lead V3R and V4R or ST elevation greater than or equal to 1 mm in lead V1 was much lower. ST segment elevation in the right precordial leads was short lived, having disappeared within 10 hours after the onset of chest pain in half of our patients with right ventricular involvement. When electrocardiograms are recorded in patients with an acute inferior wall infarction within 10 hours after the onset of chest pain, additional right ventricular infarction can easily be diagnosed by recording lead V4R.